2009
DOI: 10.4104/pcrj.2009.00018
|View full text |Cite
|
Sign up to set email alerts
|

Middle lobe syndrome in the left lower lobe in chronic obstructive pulmonary disease

Abstract: Middle lobe syndrome is a term that refers to a recurrent collapse of a lung segment, typically the right middle lobe. We discuss a case that middle lobe syndrome occurred in an unusual lung segment and related to an unusual cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…If obstructive, surgery is needed to remove the cause or the entire lobe. In non-obstructive MLS, a medical approach is preferred, with bronchodilator and mucolytic agents, respiratory kinesiotherapy and immunostimulants [1, 2,1618] .…”
Section: Discussionmentioning
confidence: 99%
“…If obstructive, surgery is needed to remove the cause or the entire lobe. In non-obstructive MLS, a medical approach is preferred, with bronchodilator and mucolytic agents, respiratory kinesiotherapy and immunostimulants [1, 2,1618] .…”
Section: Discussionmentioning
confidence: 99%
“…6 Infectious causes are most commonly bacterial, but can be viral, mycobacterial, or fungal. 7 It has been hypothesised that right middle lobe is relatively isolated lobe with lack of collateral ventilation from other lobes. Complete fissures surround the RML resulting in absence of collateral ventilation, leading to atelectasis, chronic inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Sekerel et al [16] reported MLS in all pulmonary segments except the left upper lobe in children with bronchial asthma. Blaivas and Strauss [17] reported a case of MLS in the left lower lobe in a case of COPD. Others reported its occurrence in the lingua as well as the right upper lobe [1,18].…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, if atelectasis persisted or recurred, resection would be indicated. This strategy has been followed by several authors and its efficacy was proved in both paediatric and adult patients [10,17]. With this approach, only about one-third of patients required surgical resection [23].…”
Section: Discussionmentioning
confidence: 99%